(untitled) (Groundings Undergraduate, 2016)
This article explores the development of West Indian cultural identity through its expression in poetry from and about the West Indies. Early forms of cultural expression from the Anglophone Caribbean were frequently realised through mimicry of British poetic forms, themes, and language. Later post-Independence poetry frequently denounced such reverence and aimed to identify the West Indian poetic voice with a conception of ‘Africa’ as an alternative parent culture. Ultimately however, neither Africa nor Britain provides a suitable comparison for the fragmented and diverse West Indies. Rather, the most apt expressions of West Indian cultural identity are found in poetry which focuses on racial hybridity, West Indian landscapes, and local dialects.